Effect of carburizing time on mechanical properties of fe-24mn steel / Muhammad Aqeel Rusdi - Rusdi, Muhammad Aqeel (2017)
High Manganese steels is a type of steel that have highly desirable properties exhibiting both high strength and good ductility especially in a sheet form. This steel is widely used in industrial - M process, it was observed that the mechanical properties and microstructure of Fe-24Mn steels were found to be influenced by pack carburizing process. Carburizing for longer times (1 to 3 hours) provided improvement on mechanical properties of Fe-24Mn steel such as ductility, ultimate tensile strength and micro-hardness of the specimen even though the ultimate tensile strength value is still lower than uncarburized Fe-24Mn steel. The study also proves the carburizing process on Fe- M α-austenite (at surface) an ε-martensite (at core). Finally, the specimen that has been carburized for 3 hours produced best result in overall.